2022
DOI: 10.3390/separations9070174
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Capture over Activated Carbon Derived from Pulverized Semi-Coke

Abstract: Pulverized semi-coke was employed as raw material to prepare activated carbon via steam activation and evaluated as a CO2 adsorbent. The effects of the preparation parameters including demineralization, activation temperature, activation time and steam flow on the structure and performance of the synthesized activated carbon were investigated. It was found that the microporous structure of activated carbon was greatly influenced by demineralization order and activation conditions. Demineralization before activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The demineralization before activation could effectively remove the removal of inorganic components, resulting in a great improvement of the microporous structure of AC, indicating that the demineralization sequence and activation conditions had a great influence on the microporous structure of AC. When compared to commercial AC, powdered semicoke AC with a narrow microporous (0.55 nm) distribution showed better cycling performance and a higher CO 2 /N 2 selectivity (34.4), proving that pore sizes smaller than 1 nm are advantageous for CO 2 adsorption . Because anthracite is relatively inexpensive, has a high carbon content, and is highly pure, research has been done on using it as a precursor for AC. Boujibar et al prepared AC from natural coal by simple chemical activation with KOH and NaOH, respectively.…”
Section: Porous Carbons For Carbon Capturementioning
confidence: 99%
See 1 more Smart Citation
“…The demineralization before activation could effectively remove the removal of inorganic components, resulting in a great improvement of the microporous structure of AC, indicating that the demineralization sequence and activation conditions had a great influence on the microporous structure of AC. When compared to commercial AC, powdered semicoke AC with a narrow microporous (0.55 nm) distribution showed better cycling performance and a higher CO 2 /N 2 selectivity (34.4), proving that pore sizes smaller than 1 nm are advantageous for CO 2 adsorption . Because anthracite is relatively inexpensive, has a high carbon content, and is highly pure, research has been done on using it as a precursor for AC. Boujibar et al prepared AC from natural coal by simple chemical activation with KOH and NaOH, respectively.…”
Section: Porous Carbons For Carbon Capturementioning
confidence: 99%
“…When compared to commercial AC, powdered semicoke AC with a narrow microporous (0.55 nm) distribution showed better cycling performance and a higher CO 2 /N 2 selectivity (34.4), proving that pore sizes smaller than 1 nm are advantageous for CO 2 adsorption. 52 Because anthracite is relatively inexpensive, has a high carbon content, and is highly pure, research has been done on using it as a precursor for AC. Both agricultural wastes and industrial byproducts or some natural carbon resources can be used as precursors for the preparation of AC, and more advanced activation methods can be used to prepare AC adsorbents with better carbon capture performance than commercial AC.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In steam activation, a large amount of steam and char react to form CO and H 2 , thus forming a developed pore structure. The reaction mechanism is shown in eq . , As shown in Figure , the reaction process is summarized as follows: The steam first diffuses to the char surface and is adsorbed by active sites in the char. The gasification reaction takes place to form the pore structure.…”
Section: Preparation Of Cacmentioning
confidence: 99%
“…Muthmann et al also found that the BET specific surface area and total pore volume of CAC increased with increasing activation time during the steam activation process. Jing et al used Hulunbuir lignite semicoke carbonized at 650 °C as a raw material to prepare AC by steam activation; they comprehensively considered the effects of activation time, activation temperature, and steam flow rate on the structure and performance of AC and determined the optimal activation conditions: the activation time was 70 min, the activation temperature was 700 °C, and the steam flow was 150 mL/min. It was found that the BET specific surface area and iodine value of AC increased with increasing activation time within 30 to 70 min, but when the activation time exceeded 70 min, the micropore structure was destroyed to form large pores, resulting in decreases in the BET specific surface area and iodine value.…”
Section: Preparation Of Cacmentioning
confidence: 99%
See 1 more Smart Citation